2014
DOI: 10.3389/fonc.2014.00038
|View full text |Cite
|
Sign up to set email alerts
|

Radioembolization and the Dynamic Role of 90Y PET/CT

Abstract: Before the advent of tomographic imaging, it was postulated that decay of 90 Y to the 0+ excited state of 90Zr may result in emission of a positron–electron pair. While the branching ratio for pair-production is small (~32 × 10−6), PET has been successfully used to image 90 Y in numerous recent patients and phantom studies. 90 Y PET imaging has been performed on a variety of PET/CT systems, with and without time-of-flight (TOF) and/or resolution recovery capabilities as well as on both bismuth-germanate and lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 57 publications
0
58
1
6
Order By: Relevance
“…Kokabi et al (2) found significantly greater tumor uptake for 99m Tc-MAA doses than for glass 90 Y microspheres (1.4:1). Among other factors, particle size, density, and morphology have been identified as key factors in these differences (3,4).…”
mentioning
confidence: 99%
“…Kokabi et al (2) found significantly greater tumor uptake for 99m Tc-MAA doses than for glass 90 Y microspheres (1.4:1). Among other factors, particle size, density, and morphology have been identified as key factors in these differences (3,4).…”
mentioning
confidence: 99%
“…Several studies [30, 31] have described changes in tumor volume and SUV in 18 FDG PET/CT when respiratory gating was used. However, investigation into the feasibility of respiratory gating in 90 Y PET/CT has been limited to a few examples [32, 33]. The usefulness of 90 Y PET respiratory gating may be limited by the small branching ratio of positron emission in 90 Y [34] and the clinical difficulty of increasing an already long acquisition time.…”
Section: Discussionmentioning
confidence: 99%
“…Comme c'est le cas pour l'ensemble des radiopharmaceutiques, les laboratoires nationaux de métrologie ont pour mission d'établir une traçabilité métrologique entre les références nationales et les utilisateurs tels que les services de médecine nucléaire [3]. L'intérêt de l'étude était également de répondre aux besoins d'une traçabi-lité métrologique en imagerie quantitative par tomographie, utilisée pour l'estimation de la biodistribution des microsphères marquées avec 90 Y après injection théra-peutique [4] pour le développement d'une dosimétrie personnalisée [5], et d'aller vers une meilleure connaissance de la relation dose-effet thérapeutique.…”
Section: Contexte Et Objectif De L'étudeunclassified